1980
DOI: 10.1111/j.1748-1716.1980.tb06533.x
|View full text |Cite
|
Sign up to set email alerts
|

The locomotion of the low spinal cat I. Coordination within a hindlimb

Abstract: Kittens were subjected to a complete transection of the spinal cord (Th 10--12) 1--2 weeks after birth. A few days after the operation they could perform alternating limb movements and somewhat later walking movements with their hindlimbs on a treadmill. The stepcycle of the hindlimbs could be divided into a flexion phase (F) and a first (E1), second (E2) and third (E3) extension phase. The duration of the support phase decreased markedly with treadmill velocity while the swing phase decreased to a much smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(104 citation statements)
references
References 38 publications
4
95
0
Order By: Relevance
“…The present results clearly demonstrate that phasedependent gating of motor-evoked responses can be mediated by the spinal locomotor circuitry. These data are remarkably similar to the phase-dependent cutaneous reflex reversal observed when spinal cats are tripped (Forssberg et al, 1980).…”
Section: Phase-dependent Modulation Of Motor-evoked Potentialssupporting
confidence: 76%
“…The present results clearly demonstrate that phasedependent gating of motor-evoked responses can be mediated by the spinal locomotor circuitry. These data are remarkably similar to the phase-dependent cutaneous reflex reversal observed when spinal cats are tripped (Forssberg et al, 1980).…”
Section: Phase-dependent Modulation Of Motor-evoked Potentialssupporting
confidence: 76%
“…36 The main objective of the present study was to measure how SCI subjects adapt to changes in the walking speed. Studies of hindlimb locomotion in spinalized cats [37][38][39] have shown that adaptation to increasing treadmill speed was possible, but that this adaptation was limited to a maximal speed varying between 0.8 and 1.0 m/s. In the spinal cat, the limited adaptation to increases in speed is presumably because of the absence of descending tracts and achieved with input solely from peripheral influence.…”
Section: Discussionmentioning
confidence: 99%
“…The breakthrough of rehabilitative training following SCI is based on studies in cats, showing that following complete transection a locomotor pattern could be initiated in the paralyzed hindlimbs [36,37]. Although no connection to the brain existed, this locomotor "recovery" could be amplified with treadmill training, ultimately resulting in weight-supported stepping on a treadmill [38,39].…”
Section: Activity-based Approachesmentioning
confidence: 99%